Development of Stability Indicating UV-Method for The Determination of Artesunate in Bulk and Pharmaceutical Dosage Form - Gangu Sreelatha; J.S Swatantra; E. Ratna Sri; Ch. Samatha; G. BhagyaLaxmi (International Journal of Pharma and Bio Sciences, 2024)
Most of the inorganic arsenic consumed through contaminated drinking water is absorbed through the intestinal walls and thentransported to liver cells, thus causing toxic damage to the liver. Arsenic poisoning leads to irreversible damage to the kidneys.Arsenic damages the capillaries, tubules, and glomeruli of the kidney. Arsenic toxicity causes mild to severe necrosis anddegenerative changes in the kidney, with contracted glomeruli cells and increased Bowman's space. The present study has analyzedthe effect of oral treatment of T. aestivum leaf extract to counteract nephrotoxicity induced by arsenic intake in adult Swiss albinomice. Biochemical parameters were performed in kidney tissue after isolation from Swiss albino mice. Blood collection was donefrom the ventricle of the heart immediately after cervical dislocation and autopsy of mice. Kidney function tests were performedin serum isolated from blood. These animals were divided into various groups for experimentation. In the control group, puredouble distilled water was given as a vehicle. An oral dose of 20 ml/kg b.wt. has been provided in the Triticum aestivum treatmentgroup. An oral dose of 4.0 mg/kg b.wt has been provided to the Sodium arsenite (NaAsO2) intoxicated group.In combinationwith treated animals, T. aestivum was given orally before and after oral intoxication of NaAsO2. Activities of antioxidant enzymessuch as GSH glutathione), LPO (lipid peroxidation), enzymes indicating tissue damage such as ALP (alkaline phosphatase), ACP(acid phosphatase), LDH (lactate dehydrogenase), serum urea, serum creatinine, and serum uric acid content were calculated inthe kidney. The present study's findings indicate that arsenic intoxication substantially increases in serum creatinine, ACP, LPO,serum urea, and serum uric acid. In contrast, it substantially declines LDH, GSH, and ALP activities. Collective exposure of NaAsO2and T. aestivum depicted (i) a substantial decrease in LPO, creatinine, ACP, serum urea, and uric acid activities and (ii) an uplift inactivities of LDH, ALP, and GSH in contrast to NaAsO2 exposure. Results indicate that Wheatgrass protects against renal damagedue to arsenic toxicity. The present study concludes that T. aestivum can scavenge free radical species and peroxides produced inthe kidney of Swiss albino mice and show a modulatory effect against arsenic-induced nephrotoxicity.